2002
DOI: 10.1046/j.1440-1819.2002.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow changes in general paresis following penicillin treatment: A longitudinal single photon emission computed tomography study

Abstract: Three cases of general paresis were successfully treated with high-dose penicillin. In all cases, cerebrospinal fluid cell counts decreased to normal and mental status improved rapidly. Cerebrospinal fluid protein concentrations decreased and IQ scores and overall levels of functioning improved gradually over 1 year. Regional cerebral blood flow (CBF) changes were analyzed longitudinally for 1 year using single photon emission computed tomography (SPECT). Autoradiography method and region of interest (ROI) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The perfusion of the regions of interest and glucose metabolism were found to be increased. After penicillin G (24 million units/day for 21 days) treatment, the perfusion and glucose metabolism were decreased [ 43 ]. This was the same as other changes in acute encephalitis, that focal unilateral hyper-perfusion was an indicator of severe inflammation of the brain tissue [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The perfusion of the regions of interest and glucose metabolism were found to be increased. After penicillin G (24 million units/day for 21 days) treatment, the perfusion and glucose metabolism were decreased [ 43 ]. This was the same as other changes in acute encephalitis, that focal unilateral hyper-perfusion was an indicator of severe inflammation of the brain tissue [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that there was local hoperperfusion in AD patients [17], but whether there is CBF change in GP has not been reported. To the best of our knowledge, the research on CBF in GP is limited to the change of CBF before and after penicillin treatment [18]. Kitabayashi had reported that quantitative CBF remarkably decreased in GP patients following penicillin treatment, meanwhile, the CSF cell count decreased and the mental status the decrease of CBF indicates the disappearance of encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that WMH of GP patients was mainly focused in the frontal cortex, bilateral temporal and periventricular areas; therefore, their attention networks may have been greatly influenced. After penicillin therapy, the slow recovery of cerebral blood flow (YurinosukeKitabayashi et al, 2002) may result in the a reduction of WMH area and contribute to the resumption of attention network of GP patient. However, the Fazekas scale scores were not an effective predictor of clinical outcomes in our study.…”
mentioning
confidence: 99%